HUBUNGAN INSENTIF DENGAN KINERJA PERAWAT BERDASARKAN STATUS KEPEGAWAIAN DIRUANG RAWAT INAP RSUD PRINGSEWU TAHUN 2019 - Yenny Marthalena; Surmiarsih Surmiarsih; Moch Alfan Nuruddin (Jurnal Signaling, 2020)
Incentives are a form of reward or service provided by an organization or employee, performance is a picture of the level of achievement of the implementation of an activity program in realizing the vision and mission of the organization. So that there is the effect of giving incentives, leadership and workload on nurse performance. The enthusiasm for employee performance can be caused by the size of the incentives received. This study aims to determine the relationship of incentives with performance based on employment status in the inpatient room of Pringsewu Hospital in 2019.This type of research is quantitative, cross sectional design. The population is all employees in the room of the male RPD, the female RPD, the surgical room, the children's room, which amounted to 56 respondents. The sample uses total sampling. Bivariate analysis in this study used the Gamma test. The results showed that there was no relationship between incentives and performance because the significance values and result Honorer ρ value 0,080 . The expected that hospital management conducts a comprehensive evaluation of policies in the provision of incentives with adjusted performance.